2021
DOI: 10.1111/bjh.18012
|View full text |Cite
|
Sign up to set email alerts
|

Eltrombopag in paediatric immune thrombocytopenia: Iron metabolism modulation in mesenchymal stromal cells

Abstract: Summary Immune thrombocytopenia (ITP) is an autoimmune disease caused by platelet destruction mediated by auto‐antibody production. It is characterized by a compromised immune system and alteration of the inflammatory response. Mesenchymal stromal cells (MSCs) play an important role in modulating immune and inflammatory processes, exerting immune‐suppressing and anti‐inflammatory properties. In ITP‐MSCs the activity and survival are strongly impaired. Eltrombopag (ELT) is a thrombopoietin receptor agonist appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 35 publications
(150 reference statements)
3
22
0
Order By: Relevance
“…Moreover, in line with past work by Spitz et al 7 who demonstrated that ELT is a direct inhibitor of pro-apoptotic BAX, Di Paola et al 1 also found moderately reduced apoptosis rates in MSC and a strong upregulation of anti-apoptotic BCL-2 following ELT treatment. Whether the reduced ferric iron content in ITP-MSC contributes to differential regulation of BCL-2, changes in cell survival, or any other cell functions upon ELT treatment remains to be determined.…”
supporting
confidence: 80%
See 3 more Smart Citations
“…Moreover, in line with past work by Spitz et al 7 who demonstrated that ELT is a direct inhibitor of pro-apoptotic BAX, Di Paola et al 1 also found moderately reduced apoptosis rates in MSC and a strong upregulation of anti-apoptotic BCL-2 following ELT treatment. Whether the reduced ferric iron content in ITP-MSC contributes to differential regulation of BCL-2, changes in cell survival, or any other cell functions upon ELT treatment remains to be determined.…”
supporting
confidence: 80%
“…This study 1 provides proof‐of‐concept data supporting aberrant iron loading of MSC in ITP; it sheds further light on the mechanistic underpinnings of ELT in this disease, which may also be a starting point to better understand the absence of cross‐resistance to TPO‐RA in ITP 12 ; and it suggests that ELT may be beneficial for normalising the immune modulatory activities and survival of MSC in patients, which may provide another path to curtailing abnormal immune function in ITP. Further work will need to address the prevalence of iron loading in MSC of patients with ITP and validate the authors’ findings in vivo.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Eltrombopag (ELT) is an orally available thrombopoietin receptor agonist responsible for the stimulation of platelet production, currently approved for the treatment of chronic immune thrombocytopenia when both first-line therapy and splenectomy fail [ 101 , 103 , 104 ]. It is also used in refractory aplastic anemia, and in patients with thrombocytopenia secondary to hepatitis C during treatment with interferon [ 104 ].…”
Section: Eltrombopag As An Anti-inflammatory Moleculementioning
confidence: 99%